Are Increasing Volumes of Children and Young People Presenting to Emergency Departments Due to Increasing Severity of Illness?. (19th April 2017) - Roland, Damian; Jones, Sam; Coats, Tim; Davies, Ffion
Abstract : Background: Increasing utilization of emergency and acute care services by children and young people is a worldwide trend. This is thought to be a result of parent and carer desire for more "on‐demand" healthcare assessment and not a consequence of increasing severity of disease. A bespoke acuity assessment system in our department allowed us to test this hypothesis. Methods: These data are based on the Paediatric Observation Priority Score, a previously published and validated assessment tool designed specifically for pediatric emergency care. 1 It is scored from 0 to 16 and consists of physiologic, observational, and historical components with a unique "gut feeling" element. Data were available from November 2014 to March 2016. Results: There has been a 32.6% increase in the number of children with a POPS > 4 (Figure 1, total number of children with POPS 0, 1–4, and >4) with a small (nonsignificant) increase in relative acuity. Conclusion: In light of the overall total increase in attendances and relative increase in acuity it appears the general cohort of children presenting are more unwell. Given that a POPS > 4 is associated with an increased risk of admission for more than 24 hours 2 it can also be concluded that a significant proportion of attendances to the department are appropriate. Figure 1 Total number of children with POPS 0, 1‐4 and >4.